Thermal stress analysis of functionally graded annular fin - Yıldırım, Ali; Yarımpabuç, Durmuş; Celebi, Kerimcan (Journal of thermal stresses, 2019)
Thermal stress distributions in an annular fin with rectangular profile made of functionally graded material (FGM) are considered. The material properties of annular fin are assumed to be graded along the fin radius as a power-law function while the Poisson's ratio is taken to be constant. The governing equations are solved analytically for specific value of inhomogeneity parameter of thermal conductivity and all numerical values of inhomogeneity parameters of modulus of elasticity and linear thermal expansion coefficient. The effect of the inhomogeneity parameters on temperature distribution and thermal stresses are presented in graphical form. The formulation is validated with benchmark results in the literature. It is also shown that functionally graded annular fin is subject to lower stresses, although it has higher tip temperature than the homogeneous one.